2021
DOI: 10.18860/jeasp.v4i1.12618
|View full text |Cite
|
Sign up to set email alerts
|

The Students’ Perception of Extensive Reading in Online Learning at FLSP Class

Abstract: The purpose of this research aimed to know the students’ perception on their online Extensive reading learning. Survey design was used to conduct this study, and therefore, the questioner was constructed as the instruments of the study besides the researcher himself. The participants of this research were 44 students of first semester in the Accounting Department at FLSP class of University of Muhammadiyah Malang (Class A). The researcher adopted the questionnaire from a previous study conducted by Yogurtcu (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Teachers must incorporate instructional technology because it is essential in today's education industry (Edi, 2023). These situations are standard, as students and teachers can easily access online learning platforms (Raunaq et al, 2021).In the previous study, another researcher explored students' self-directed learning in listening skills using live worksheets.…”
Section: Discussionmentioning
confidence: 99%
“…Teachers must incorporate instructional technology because it is essential in today's education industry (Edi, 2023). These situations are standard, as students and teachers can easily access online learning platforms (Raunaq et al, 2021).In the previous study, another researcher explored students' self-directed learning in listening skills using live worksheets.…”
Section: Discussionmentioning
confidence: 99%
“…During the pandemic, Raunaq et al (2021) investigated Indonesian accounting students' perception of their online extensive-reading and found that students showed a positive response towards the use of extensive-reading in online learning. Likewise, Howshigan and Nadesan (2021) examined accounting students' perceptions of online learning in Sri Lanka and found that students were satisfied with online learning; however, they preferred face-to-face learning more.…”
Section: Studies Related To Online Students' Perceptionsmentioning
confidence: 99%
“…Research has demonstrated positive effects on several cognitive and affective factors (Takase, 2007;Yamashita, 2008). The implementation of extensive reading helps students develop good reading habits and fluency (Stoller, 2015) and critical thinking (Faridah & Rukminingsih, 2021;Yunus & Ubaidillah, 2021), build up their vocabulary knowledge (Anindita, 2020;Krashen, 1989;Liu & Zhang, 2018;Webb & Chang, 2015) and enhance positive reading attitudes (Fithriani et al, 2020;Lekawael & Ferdinandus, 2021;Liu & Zhang, 2018;Novita & Setiawan, 2020;Permatasari et al, 2020;Raunaq et al, 2021). Further, Liu, and Zhang (2018) showed students at the university level got the highest impact from the Extensive Reading implementation.…”
Section: Introductionmentioning
confidence: 99%